Elevated plasma zonulin and CAF22 are correlated with sarcopenia and functional dependency at various stages of Alzheimer's diseases. (November 2022) - Karim, Asima; Iqbal, M. Shahid; Muhammad, Tahir; Ahmad, Firdos; Qaisar, Rizwan
Abstract: Age-related muscle decline, termed sarcopenia, is closely linked to dementia; however, its causative factors in patients with Alzheimer's disease (AD) are poorly characterized. We investigated the plasma biomarkers of increased intestinal permeability (zonulin) and neuromuscular junction (NMJ) disruption (c-terminal agrin fragment-22; CAF22), in healthy controls (n = 53) and patients with early, mild, and moderate AD (n = 46–56/group). We also evaluated the body composition, handgrip strength (HGS), and short physical performance battery (SPPB) as markers of sarcopenia and functional capacity, respectively. Patients with AD had elevated plasma zonulin and CAF22, along with reduced HGS, gait speed, and SPPB scores than controls (all p < 0.05). Plasma zonulin and CAF22 exhibited robust negative associations with HGS and relatively weak but statistically significant associations with gait speed and ASMI (all p < 0.05). Lower SPPB scores were associated with elevated plasma zonulin and CAF22 levels. Patients with moderate AD had higher plasma zonulin, CAF22, prevalence of sarcopenia, and lower HGS and SPPB scores than patients with early AD. These patients also presented with upregulation of markers of inflammation and oxidative stress. Altogether, AD was associated with an advanced sarcopenia phenotype, and plasma zonulin and CAF22 may be useful in assessing sarcopenia and functional dependency in AD patients. Highlights: Elderly patients with Alzheimer's disease (AD) present with muscle loss or sarcopenia. Plasma zonulin and CAF22 levels are elevated in AD patients. Intestinal leak and neuromuscular junction disruption may account for sarcopenia in AD.